Molecular Detection of Coxiella burnetii in Ticks Isolated from Domestic Animals in Slaughterhouses and Farms, Shahr-E-Rey, Tehran, Iran - Pedram Talaie; Maryam Tavassoli; Ehsan Mostafavi; Zakiyeh Telmadarraiy; Mahdi Rohani; Saber Esmaeili; Mohammad Mehdi Sedaghat (Journal of Arthropod-Borne Diseases)
Background: Coxiella burnetii causes Q fever, a zoonotic and vector-borne disease. Ticks serve as vectors for this bacterium. This study aimed to determine the prevalence of C. burnetii infection in ticks in Shahr-e-Rey County, Tehran Province.